Social Protection in the â€œBlack Swanâ€ Era: Policy Implementation of a Village Funding Cash Transfer - Denny Iswanto; Sjamsiar Sjamsuddin; Fadillah Amin (Wacana Journal of Social and Humanity Studies, 2021)
The existence of the COVID-19 outbreak as a global pandemic is a health problem in all countries in the world, including Indonesia. This problem occurs suddenly and the impact has never been predicted which is multidimensional, resulting in an uncertain situation. In the social aspect, the existence of this pandemic has increased social problems, such as an increase in the unemployment rate and an increase in the national poverty rate. For this reason, the government has made a number of policies in the context of social protection through social safety nets, one of which is the Village Fund Direct Cash Assistance (BLT) program. The purpose of this study was to determine and analyze the implementation of the Village Fund BLT policy as social protection for the poor who are socio-economically affected by Covid-19. This research uses qualitative research with a descriptive approach. The results showed that there were still a number of problems in the implementation of the Village Fund BLT policy, including the problem of data availability and the readiness of related government institutions. For this reason, an up to date social assistance data collection system and more guidance to the village government are needed to be able to manage the Village Fund BLT system. With this research, it is hoped that it can become a material for evaluating the government in providing social protection in an accountable, effective and targeted manner.